1972
DOI: 10.1111/j.1471-4159.1972.tb01351.x
|View full text |Cite
|
Sign up to set email alerts
|

THE PURIFICATION AND PROPERTIES OF BOVINE PINEALS‐ADENOSYLMETHIONINE:N‐ACETYLSEROTONINO‐METHYL TRANSFERASE

Abstract: Abstract— Bovine pineal gland S‐adenosylmethionine: N‐acetylserotonin O‐methyltransferase has been purified about 2800‐fold using cell fractionation, ammonium sulphate treatment, Sephadex G‐200 gel filtration and anion exchange chromatography. The enzyme has been found to be a polymer; the smallest unit observed had a mol. wt. of 21,800 and the other polymers' molecular weights were multiples of this figure. In the gland extract polymers of 83,000, 100,000, 125,000 and 150,000 mol. wt. were more abundant than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The specific enzyme activities of the final preparations of bovine and chicken enzymes were 47.1 and 185 nmol melatonin formed/min/mg protein, respectively. The specific activity of our bovine enzyme was comparable with or higher than those reported by other laboratories (Jackson and Lovenberg, 1971 ;Karahasanoglu and Ozand, 1972; Kuwano and Takahashi, 1978). Chicken enzyme had a specific activity four times higher than bovine enzyme.…”
Section: Hiomt Purificationsupporting
confidence: 88%
See 2 more Smart Citations
“…The specific enzyme activities of the final preparations of bovine and chicken enzymes were 47.1 and 185 nmol melatonin formed/min/mg protein, respectively. The specific activity of our bovine enzyme was comparable with or higher than those reported by other laboratories (Jackson and Lovenberg, 1971 ;Karahasanoglu and Ozand, 1972; Kuwano and Takahashi, 1978). Chicken enzyme had a specific activity four times higher than bovine enzyme.…”
Section: Hiomt Purificationsupporting
confidence: 88%
“…Most of these studies, however, were carried out using a crude supernatant of pineal glands. HIOMT has been purified to a high degree only from bovine pineal gland (Jackson and Lovenberg, 1971; Karahasanoglu and Ozand, 1972;Ku-wan0 and Takahashi, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of reports have indicated that several forms of HIOMT exist in the pineal gland (Jackson & Lovenberg, 1971;Karahasanoglu & Ozand, 1972;Cremer-Bartels, 1979) and these various forms may have differing substrate specificities (Cremer-Bartels, 1979). As it has been shown that methoxyindoles other than melatonin exert physiological activity (Mullen, Leone, Hooper et al 1979;Pevet, 1983) and that seasonal variations in synthesis of methoxyin¬ doles exist (Balemans, Bary, van Benthem & Leger¬ stee, 1981) it may be suggested that the pineal gland controls certain physiological functions by variation in methoxyindole synthesis.…”
Section: Introductionmentioning
confidence: 98%